2010
DOI: 10.1111/j.1467-7652.2010.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to cold: transcriptome analysis of wheat

Abstract: SummaryTemperature and light are important environmental stimuli that have a profound influence on the growth and development of plants. Wheat varieties can be divided on the basis of whether they require an extended period of cold to flower (vernalization). Varieties that have a requirement for vernalization also tend to be winter hardy and are able to withstand quite extreme subzero temperatures. This capacity, however, is not constitutive and plants require a period of exposure to low, non-freezing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
197
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(209 citation statements)
references
References 151 publications
(216 reference statements)
9
197
0
3
Order By: Relevance
“…Cold acclimation leads to large-scale transcriptome changes that program the production of an array of proteins to help plants surviving freezing stress (Kocsy et al 2010;Winfield et al 2010). Recent studies describing full genome transcripts and mutational and transgenic plant analysis have provided a great deal of information about the complex transcriptional system that functions under cold acclimation (Jan et al 2009).…”
Section: Cold Acclimation and Frost Stress Tolerancementioning
confidence: 99%
“…Cold acclimation leads to large-scale transcriptome changes that program the production of an array of proteins to help plants surviving freezing stress (Kocsy et al 2010;Winfield et al 2010). Recent studies describing full genome transcripts and mutational and transgenic plant analysis have provided a great deal of information about the complex transcriptional system that functions under cold acclimation (Jan et al 2009).…”
Section: Cold Acclimation and Frost Stress Tolerancementioning
confidence: 99%
“…During cold acclimation, plants undergo large-scale changes in their transcriptome, which in turn activates the production of an array of proteins to aid the plant's survival during subsequent freezing stress (Kocsy et al 2010;Winfield et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Functional predictions of transcript sequences suggested that cold hardening affected the activity of genes involved in photosynthesis, which is characteristic of cold acclimated plant tissues [14,43,44]. One glucan endo-1,3-beta-glucosidase transcript was also found to be upregulated.…”
Section: Discussionmentioning
confidence: 99%